Dragons Love Tacos 2 : the Sequel - Rubin, Adam 1983-; Salmieri, Daniel 1983- (New York, NY : Dial Books for Young Readers, 2017)
"When dragons run out of tacos, they travel back in time to get a fresh supply"--
Keywords: Dragons -- Juvenile fiction; Tacos -- Juvenile fiction; Food habits -- Juvenile fiction; Dragons -- Fiction; Tacos -- Fiction; Food habits -- Fiction; Humorous Stories